2017
DOI: 10.1111/scd.12245
|View full text |Cite
|
Sign up to set email alerts
|

Dental fear among transgender individuals ‐ a cross‐sectional survey

Abstract: Aims: The aims of this study were to 1) evaluate the level of dental fear among transgender individuals, and 2) investigate specific predictors of dental fear in individuals who identify as transgender. Method and results: An anonymous survey among transgender adults was conducted using both a web based and paper survey. The survey included the Dental Fear Survey (DFS), history of hormonal interventions, perceived gender roles, and demographic information. The bivariate analyses did not show a significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
(54 reference statements)
0
19
0
2
Order By: Relevance
“…Robinson et al [ 26 ] indicated that sex differences in reported pain may be attributed to underlying differences in psychosocial factors. In case of the transgender patient, the fear of discrimination/maltreatment can potentially impact fear of pain, and medical professionals should be aware of this important issue and address it appropriately [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robinson et al [ 26 ] indicated that sex differences in reported pain may be attributed to underlying differences in psychosocial factors. In case of the transgender patient, the fear of discrimination/maltreatment can potentially impact fear of pain, and medical professionals should be aware of this important issue and address it appropriately [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Heima and colleagues evaluated dental fear and its predictors among transgender individuals and found that their fear and experiences of discrimination and maltreatment were positively associated with fear in the dental setting . Nevertheless, there is general paucity of data regarding general health disparities between the LGBT and heterosexual populations and virtually no data exist regarding oral health‐specific disparities.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to an increase in oral health diseases among patients with special needs; if not managed properly, these diseases are costly to governments and patients. Researchers have indicated that individuals with special health care needs are at elevated risk of developing dental complications, as compared to other individuals 2–4. Moreover, the predoctoral curricula for treating patients with special needs are inadequate 5.…”
mentioning
confidence: 99%